Determinants of educational accomplishment of migrants in Mexico City - Santiago-Hernández, Julio (Papeles de Población; Vol. 23 Núm. 92 (2017), 2018)
The purpose of this paper is to analyze the effect of immigration status on the age at which migrants exit formal schooling and their educational attainment. The aim of this work is to identify if the observed differences are due to the immigration status itself or derived from other sociodemographic variables associated with their status, a condition that could place migrants at an educational disadvantage with respect to Mexico City natives. To further investigate, we used data from the 2009 Inequality and Social Mobility Survey of Mexico City and found out that unlike the evidence of research made in the 1970s, which assumed that upward mobility was a phenomenon present in both migrant and native individuals, migrants’ educational performance is not as good as that of the natives, not just for the fact that they are migrants but because they tend to have lower economic, cultural and social capital attributes within their families of origin, a condition that prevents them from taking better advantage of their efforts to attain a similar or higher educational performance to the one of the natives. Another finding suggests that even after controlling for the disadvantageous social origin, rural migrant women maintain a consistently unfavorable performance when compared to the performance of the natives.